The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1037/pspp0000259
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept clarity lays the foundation for self-continuity: The restorative function of autobiographical memory.

Abstract: The current research concerns the relations among self-concept clarity, autobiographic memory, and self-continuity. We hypothesized, and tested in 7 studies, that low self-concept clarity would disrupt self-continuity, but resorting to autobiographic memory would counter this disruption, thus restoring self-continuity. In Studies 1 and 2, low or threatened self-concept clarity was associated with decreased, or led to a decrease of, self-continuity. In Study 3, participants low (vs. high) in self-concept clarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 78 publications
3
20
0
1
Order By: Relevance
“…In LTC patients’ quality of life (QoL) decreases 92 and autonomy and personal bonding 93 are weakened 60 as a result of increased deprivation 49 . This can lead to institutionalization 59 and hospitalization 40,94 of patients, both of which are a challenge to the continuity of self 61,95 . We found that under these circumstances two selves emerge.…”
Section: Discussionmentioning
confidence: 87%
“…In LTC patients’ quality of life (QoL) decreases 92 and autonomy and personal bonding 93 are weakened 60 as a result of increased deprivation 49 . This can lead to institutionalization 59 and hospitalization 40,94 of patients, both of which are a challenge to the continuity of self 61,95 . We found that under these circumstances two selves emerge.…”
Section: Discussionmentioning
confidence: 87%
“…Self-concept clarity—a central variable for this study—is associated with well-being and adaptive functioning because it contributes to a proper estimation of efforts in goal-directed behavior, appropriate planning, and accurate insight (DeMarree & Bobrowski, 2017; Light, 2017). Moreover, it also contributes to a sense of continuity (Jiang et al, 2019) and personality development (Lodi-Smith & Crocetti, 2017), and it implies coherence between the actual and the ideal self (DeMarree & Rios, 2014). Numerous researchers indicate that individuals who score low on the Self-Concept Clarity Scale do not function optimally (for an overview, see Lodi-Smith & DeMarree, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Past-to-present self-continuity and present-to-future self-continuity have been found to be positively associated and have similar development trends over the whole life span (Rutt & Löckenhoff, 2016; Sokol & Eisenheim, 2016). Without a sense of connectedness with their past, people would find it difficult to project their present self into the future and feel connected with their future self (Iyer et al, 2008; Jiang et al, 2020, 2022). Thus, an integrative understanding of self-continuity is needed.…”
Section: Awe and Gscmentioning
confidence: 99%